Multifunctional hybrid nanomaterials for sustainable agri-food and ecosystems - Abd-Elsalam, Kamel, 1969- (Micro & nano technologies., 2020)
Multifunctional Hybrid Nanomaterials for Sustainable Agrifood and Ecosystems shows how hybrid nanomaterials (HNMs) are being used to enhance agriculture, food and environmental science. The book discusses the synthesis and characterization of HNMs before exploring agrifoods and environmental functions. It shows how novel HNMs are being used for the detection and separation of heavy metal ions, for destroying and sensing of insecticides, in managed release fertilizer and pesticide formulations, plant protection, plant promotions, purification, detection, and to control mycotoxins. Further, the book describes the use of silica-based total nanosystems, carbon nanotubes, nanocellulose-based, and polymer nanohybrids for agricultural and biological applications. This book is an important reference source for materials scientists, engineers and food scientists who want to gain a greater understanding on how multifunctional nanomaterials are being used for a range of agricultural and environmental applications. --